THE INFLUENCE OF MARKETING MIX FACTORS AND COMMUNITY CULTURE ON THE BEHAVIOR OF CONSUMER BUYING INTEREST IN THE VARIETY OF ICED COFFEE MILK AT JANJI JIWA (Universitas Dr. Soetomo, 2022)
This study aims to analyze the influence of several marketing mix factors such as product, price, location, promotion, and community culture on purchasing decisions for the Iced Coffee Milk product variant at the Janji Jiwa Cafe. The population of this research is the visitors of the Janji Jiwa Cafe Volume 65 Surabaya. Samples were taken using random sampling technique. Samples were taken as many as 100 loyal buyers of Iced Coffee Milk at the Janji Jiwa Cafe Volume 65 Surabaya who were met during the distribution of the questionnaire. Data obtained from the distribution of questionnaires. The data analysis technique used multiple linear regression and hypothesis testing using F-test and t-test. Based on the F-test, it is known that simultaneously product, price, location, promotion, and culture have a significant effect on purchasing decisions because the significance value is less than 0.05, which is 0.000. Based on the t-test, it is known that the product has a significant effect on purchasing decisions because the significance value is smaller than 0.05, which is 0.002. Price has a significant effect on purchasing decisions because the significance value is smaller than 0.05, which is 0.007. Location has a significant effect on purchasing decisions because the significance value is smaller than 0.05, which is 0.005. Promotion has a significant effect on purchasing decisions because the significance value is smaller than 0.05, which is 0.004. Meanwhile, culture has a significant effect on purchasing decisions because the significance value is smaller than 0.05, which is 0.001.